GROUNDWATER QUALITY INFLUENCING THE POTATO TUBER YIELD IN DOABA REGION OF PUNJAB, INDIA - Kumar, Prince; Sharma, Jagdev; Sharma, Anil; Garde, Yogesh; Kumar, Raj; Sharma, Vineeta; Singh, Brajesh (Potato Journal, 2024)
Groundwater as a source of irrigation is extensively practiced in the Doaba region of Punjab, alongside high inputs such as chemical fertilizers and pesticides. These inputs pose dual threats to the deterioration and deepening of groundwater. Therefore, a survey-based investigation was conducted in the region, involving the collection of groundwater samples, their physico-chemical analysis, and the assessment of harvested potato tuber yields. The data analysis revealed that farmers are extracting groundwater from borewells at a depth of 254.0 feet on average, with a delivery depth of 145.67 feet. The analytical results indicated that all the collected groundwater samples were suitable for irrigation purposes. Furthermore, there was a significantly positive correlation between tuber yield and nitrate content of groundwater. Thus, it is crucial to consider the contribution of nitrate from groundwater when recommending nitrogen usage.